THEORY OF INSTALLATION IN SPORTS ACTIVITY - Muhiddinov Abdubanob (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The main goal of the reforms being carried out in Uzbekistan is to create a healthy and well-educated generation in our country with high spiritual and moral qualities. Because physical education and sports play an important role in the growth and healthy development of young people. A healthy person develops self-confidence, perseverance, skills and qualities of being able to finish what he has started. The article examines sports activities and the theory of installation.